2016
DOI: 10.1007/s40415-016-0273-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of variation in heath vegetation structure on coastal dune fields in northeastern South America

Abstract: Despite its implications for carbon storage, animal conservation, and plant regeneration, the variation in the structure of heath vegetation in South America is still poorly studied. In this study, we aimed at examining the edaphic and topographic determinants of this variation along 85 plots (5 9 5 m) randomly distributed in a restinga heath vegetation occurring on coastal dune fields in northeastern Brazil. We carried out a PCA analysis to reduce eleven vegetation descriptors into a small number of structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A number of researchers have found that soil nutrients, aluminum content, acidity, percentage of sand, and amount of organic matter are related to changes in heath vegetation physiognomy from marsh to scrub to forest (Silva et al. ) as well as to local community structure both locally (Scarano , Santos‐filho et al. ) and regionally (Marques et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of researchers have found that soil nutrients, aluminum content, acidity, percentage of sand, and amount of organic matter are related to changes in heath vegetation physiognomy from marsh to scrub to forest (Silva et al. ) as well as to local community structure both locally (Scarano , Santos‐filho et al. ) and regionally (Marques et al.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure varies from open herbaceous vegetation on beaches and the windward slopes of sand dunes to mosaics of scrub and short forest patches on the leeward slopes of sand dunes and coastal plains (Silva et al. ). We studied heath communities along the Brazilian coast, which corresponds to ~60% of the Atlantic coast of South America and extends ~9000 km from the Oiapoque River (04.19° N, 51.60° W) to the Brazil/Uruguay border (33.70° S, 53.42° W; Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A stem vulnerability index was calculated using vessel diameter and vessel density (Scholz et al., ). The main stem length and stem diameter at soil level were obtained from Silva, Silva, and Souza ().…”
Section: Methodsmentioning
confidence: 99%